Utilization of Garlic Extract for Confectionery Products (Journal of Agriculture and Biology, 2025)
Garlic contains significant amounts of amino acids and sulfur compounds that can improve immune system against viruses responsible for colds. The current research is intended to evaluate the effects of garlic extract having antioxidant properties on the formation of confectionery products (lozenges and gummies). The products’ quality depended highly on concentration of garlic extract, sugar and flavoring agent. The percent composition of the sugar, flavoring agent and garlic extract for product lozenges were 100:0:0 for T0, 75:20:5 for T1, 75:15:10: for T2 and 75:10:15: for T3. And the percentage composition of sugar, gelatin, flavoring agent and garlic extract for product gummies were 100:0:0:0 for T0, 55:20:20:5 for T1, 55:20:15:10 for T2 and 55:20:10:15 for T3. Proximate analysis, antioxidant activity, color, pH and minerals of the sample were calculated. The results of the proximate analysis of the best lozenge sample were 32.03% moisture, 2.01% crude fat, 5.31% protein, 2.4% fiber, 2.6% ash, 30.98% DPPH, 35.56% NFE and pH were 7.0. And the results of the best gummies sample were 36.6% moisture, 1.33% crude fat, 10.09% protein, 1.5% fiber, 2.4% ash, 31.81% DPPH, 36.35.64% NFE and pH were 7.0. The mineral composition of the best one lozenge sample was 6.8 mg/l iron, 20.98 mg/l calcium and 1.23 mg/l zinc and the mineral composition of the best one gummy sample were 3.13 mg/l iron, 21.78 mg/l calcium and 3.08 mg/l zinc. With reference to sensory evaluation T2 was most preferred for lozenges and T3 for gummies. These results indicate that using garlic extract in formation of confectionery products may help to improve oral health.